Metal–Organic Framework Nanoparticles. Issue 37 (3rd June 2018) - Wang, Shunzhi; McGuirk, C. Michael; d'Aquino, Andrea; Mason, Jarad A.; Mirkin, Chad A.
Abstract: Due to their well‐defined 3D architectures, permanent porosity, and diverse chemical functionalities, metal–organic framework nanoparticles (MOF NPs) are an emerging class of modular nanomaterials. Herein, recent developments in the synthesis and postsynthetic surface functionalization of MOF NPs that strengthen the fundamental understanding of how such structures form and grow are highlighted; the internal structure and external surface properties of these novel nanomaterials are highlighted as well. These fundamental advances have resulted in MOF NPs being used as components in chemical sensors, biological probes, and membrane separation materials, as well as building blocks for colloidal crystal engineering. Abstract : Metal–organic framework nanoparticles (MOF NPs) are an emerging class of modular nanomaterials. Recent developments in the synthesis and postsynthetic surface functionalization of MOF NPs that strengthen the fundamental understanding of how such structures form and grow are highlighted; the internal structure and external surface properties of these novel nanomaterials are highlighted as well.